Electronic goods in the light of the United Nations Convention on the Contracts for the International Sale of Goods (CISG) in relation to software - Kunicka, Angelika (Wydawnictwo C.H. Beck, 2019)
This article aims to analyze the issue of applicability of software sales, especially as an electronic good in the light of the United Nations Convention on Contracts for the International Sale of Goods (CISG). The Convention was drafted in Vienna in 1980 and after being applied in 92 countries it became counted for more than 80% of international trade when it comes to goods. Although being in force over three decades, it is one of the most effective instruments for unification and harmonization that international trade has ever created. In my opinion the issue whether to apply the CISG to software transactions, especially when software is downloaded via the internet, without material character of ‘goods’, deserves special attention. Nowadays there is a conflict of interpretation of the Convention, which has risen due to an unexpected development of modern society with new technologies not taken into account when adopting. This problem had caught my attention during volunteering for the Polish Permanent Mission of the Republic of Poland to the United Nations Office and International Organizations in Vienna and led to writing this article. I realized that the progressive increase in economic trading and e-commerce brings the importance of transactions such as international sales of software. Having in mind applying the CISG to software not delivered in a tangible form I would also like to refer to the definition of ‘goods’ under the CISG and look into various types of software.
Keywords: software; CISG; applicability; electronic goods; goods; intangible; sale